"Live together, die alone": The effect of re-socialization on behavioural performance and social-affective brain-related proteins after a long-term chronic social isolation stress - Rivera, Daniela S.; Lindsay, Carolina B.; Oliva, Carolina A.; Bozinovic, Francisco; Inestrosa, Nibaldo C. (My University, 2021)
Loneliness affects group-living mammals triggering a cascade of stress-dependent physiological disorders. Indeed, social isolation stress is a major risk factor for several neuropsychiatric disorders including anxiety and depression. Furthermore, social isolation has a negative impact on health and fitness. However, the neurobiological consequences of long-term chronic social isolation stress (LTCSIS) manifested during the adulthood of affected individuals are not fully understood. Our study assessed the impact of LTCSIS and social buffering (re-socialization) on the behavioural performance and social-affective brain-related proteins in diurnal, social, and long-lived Octodon degus (degus). Thereby, anxiety-like and social behaviour, and social recognition memory were assessed in male and female animals subjected to a variety of stress-inducing treatments applied from postnatal and post-weaning until their adulthood. Additionally, we evaluated the relationship among LTCSIS, Oxytocin levels (OXT), and OXT-Ca2+-signalling proteins in the hypothalamus, the hippocampus, and the prefrontal cortex. Our findings suggest that LTCSIS induces anxiety like-behaviour and impairs social novelty preference whereas sociability is unaffected. On the other hand, re-socialization can revert both isolation-induced anxiety and social memory impairment. However, OXT and its signalling remained reduced in the abovementioned brain areas, suggesting that the observed changes in OXT-Ca2+ pathway proteins were permanent in male and female degus. Based on these findings, we conclude degus experience social stress differently, suggesting the existence of sex-related mechanisms to cope with specific adaptive challenges.
Keywords: octodon degus; chronic stress; anxiety-like behaviour; memory-oxytocin-ca2+ signalling; re-socialization